Expression of telomerase reverse transcriptase positively correlates with duration of lithium treatment in bipolar disorder. (April 2020) - Lundberg, Martin; Biernacka, Joanna M.; Lavebratt, Catharina; Druliner, Brooke; Ryu, Euijung; Geske, Jennifer; Colby, Colin; Boardman, Lisa; Frye, Mark; Schalling, Martin
Highlights: Telomerase reverse transcriptase decreases oxidative stress in mitochondria. Oxidative stress and mitochondrial dysfunction are implicated in bipolar disorder. Lithium treatment correlates with expression of telomerase reverse transcriptase. Abstract: Bipolar disorder (BD) may be associated with accelerated cellular aging. However, previous studies on telomere length (TL), an important biomarker of cellular aging, have yielded mixed results in BD. We aimed to evaluate the hypothesis that BD is associated with telomere shortening and whether this is counteracted by long-term lithium treatment. We also sought to determine whether long-term lithium treatment is associated with increased expression of telomerase reverse transcriptase ( TERT ), the catalytic subunit of telomerase. We determined TL and TERT expression in 100 BD I patients and 100 healthy controls. We also genotyped three single nucleotide polymorphisms associated with TL. TERT expression was significantly increased in BD I patients currently on lithium treatment. TERT expression was also significantly positively correlated with duration of lithium treatment in patients treated for 24 months or more. However, we did not find any significant effect of lithium treatment on TL. Neither did we find significant differences in TL between BD patients and controls. We suggest that long-term lithium treatment is associated with an increase in the expression of TERT . We hypothesize that an increase in TERT expression may contribute to lithium's mood stabilizing and neuroprotective properties by improving mitochondrial function and decreasing oxidative stress.